Social Ills and Remedies In the Risale-I Nur - Akhmetova, Elmira (2019)
This paper discusses social ills prevailed in modern times and provides solutions based on Risale-i Nur of Said Nursi. Based on the ideas of Nursi, it observes that psychological, spiritual and social problems are the main reason for the decline of the Muslim ummah and provides medicine to overcome these illnesses.